State of Urban Household Drinking Water Security Situation in Bamenda North West Region, Cameroon - Veryee, Leonard; Fon, Fombe Lawrence; Shende, Kometa Sunday (Environmental Management and Sustainable Development, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Urban water governance is a rising challenge across the third world countries where the population is increasingly combating water crisis. The situation in the city of Bamenda has obliged the population to resort to doubtful sources and is exposed to water borne diseases despite the multiple water supply systems in the city. The study aimed to assess the state of urban household drinking water in the city of Bamenda. In order to meet the objective, a total of 420 questionnaires were administered to households in the three Sub-Divisions of the city accompanied by interviews. Data was analysed by use of the Statistical Package for Social Sciences (SPSS) version 25, Microsoft excel and Microsoft word 2016. Findings reveal that, multiple water supply sources prevail in the city (pipe borne water 65%, boreholes 18.6%, wells 8.3%, and spring/stream 8.1%) with three major pipe borne water suppliers. Approximately 25% of the study population obtained water from sources located off their premises and an average of 79.9% of the 25% spend over 30 minutes trekking for over a kilometre to fetch water. There is high financial cost in acquiring home water connection with an average rate of 200,000 FCFA (333.26 U.S Dollar). Since 2005 the city population has not met the minimum water of 50 l/p/d. In order to solve the water insecurity within the city, the study proposed that all water providers should ensure transparency, accountability, participation, the development of new water infrastructures and improvement on existing ones and financial support from the state.